Long-COVID olfactory dysfunction: allele E4 of apolipoprotein E as a possible protective factor - Danilo Nunes Oliveira; José Wagner Leonel Tavares-Júnior; Werbety Lucas Queiroz Feitosa; Letícia Chaves Vieira Cunha; Carmem Meyve Pereira Gomes; Caroline Aquino Moreira-Nunes; Jean Breno Silveira da Silva; Artur Victor Menezes Sousa; Safira de Brito Gaspar; Emmanuelle Silva Tavares Sobreira; Laís Lacerda Brasil de Oliveira; Raquel Carvalho Montenegro; et al. (Arquivos de Neuro-Psiquiatria, 2024)
Background Olfactory dysfunction (OD) represents a frequent manifestation of the coronavirus disease 2019 (COVID-19). Apolipoprotein E (APOE) is a protein that interacts with the angiotensin-converting enzyme receptor, essential for viral entry into the cell. Previous publications have suggested a possible role of APOE in COVID-19 severity. As far as we know, no publications found significant associations between this disease's severity, OD, and APOE polymorphisms (E2, E3, and E4).